2018
DOI: 10.1039/c8ra01606b
|View full text |Cite
|
Sign up to set email alerts
|

A concise synthesis of (±)-7-O-galloyltricetiflavan

Abstract: (AE)-7-O-galloyltricetiflavan (1a) was synthesized successfully in five steps from the commercially available trihydroxyacetophenone (2) and trimethoxybenzoyl chloride (3). The flavone 4a was prepared in a one-pot reaction and it gave hex-O-methylflavan 6 followed by acylation and reduction. However, the demethylation of flavan 6, 5-O-acetylflavan 10 and 5-O-phenylacetylflavan 11 by BBr 3 gave all the hydrolyzed fragments 7 and 8 as the major products. By contrast, in the same condition, hept-Omethylflavan 9 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The nine known compounds were identified as patriscabratine, 42 triacetin, 43 2-methoxybenzoic acid, 44 2-hydroxy-5-methoxybenzoic acid, 45 salicylic acid, 46 4hydroxybenzoic acid, 47 capilliplactone, 48 tricin, 49 and 5,7dihydroxy-3′,4′,5′-trimethoxyflavone. 50 T h i s c o n t e n t i s Compound 1 was isolated as a white amorphous solid. Its molecular formula (C 20 H 34 O 2 ) was determined by analysis of the (+)-HRESIMS peak at m/z 329.2451 ([M + Na] + , calcd 329.2451).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nine known compounds were identified as patriscabratine, 42 triacetin, 43 2-methoxybenzoic acid, 44 2-hydroxy-5-methoxybenzoic acid, 45 salicylic acid, 46 4hydroxybenzoic acid, 47 capilliplactone, 48 tricin, 49 and 5,7dihydroxy-3′,4′,5′-trimethoxyflavone. 50 T h i s c o n t e n t i s Compound 1 was isolated as a white amorphous solid. Its molecular formula (C 20 H 34 O 2 ) was determined by analysis of the (+)-HRESIMS peak at m/z 329.2451 ([M + Na] + , calcd 329.2451).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Five previously undescribed fatty acid lactones, which consist of four 2-pyrones with long chains (passifetilactones A–D, 1 – 4 ) and one furanone with a long chain (passifetilactone E, 5 ) are herein described. The nine known compounds were identified as patriscabratine, triacetin, 2-methoxybenzoic acid, 2-hydroxy-5-methoxybenzoic acid, salicylic acid, 4-hydroxybenzoic acid, capilliplactone, tricin, and 5,7-dihydroxy-3′,4′,5′-trimethoxyflavone …”
Section: Resultsmentioning
confidence: 99%
“…7-O-Galloyltricetifavan (7OGT; figure 1), a natural flavonoid, was first isolated from the leaves of Pithecellobium clypearia [1][2][3]. 7OGT is a flavan derivative that has antiviral properties against respiratory syncytial virus, influenza H1N1 virus, herpes simplex virus type 1 and coxsackie B3 virus as well as anti-inflammatory, anti-Alzheimer, anti-allergic and antioxidant properties [1][2][3][4][5][6][7]. Studies showed that 7OGT has potent xanthine oxidase inhibition with an IC 50 = 25.5 µmol l −1 [3] and inhibits soluble epoxide hydrolase enzymatic activity with IC 50 values 10.0 ± 0.4 µM [5].…”
Section: Introductionmentioning
confidence: 99%